Kepemimpinan Kepala Sekolah Dalam Melakukan Inovasi Manajemen Pendidikan - Rasuli, Rasuli (JoEMS (Journal of Education and Management Studies), 2023)
Educational management is a science that studies how to organize resources to achieve predetermined goals productively and how to create a good atmosphere for people who participate in achieving agreed goals. In relation to educational development, school principals have a very important role and duties. This is because the school principal as a leader is one of the factors that drives progress in the world of education. The method that the author uses in writing this thesis begins with determining the research subject, then collecting data using interview, observation and documentary methods, and the data analysis used is descriptive qualitative. From the results of the research carried out, it can be concluded that (1) Regarding the leadership of the principal of MAN Kandangan Kab. Kediri, as an open and dynamic leader, is willing to accept input from his subordinates in decision making. He also has very important responsibilities, has abilities and skills, including: having the ability to organize both staff and other employees, having the ability to generate and foster confidence in himself and other teachers, having the ability to encourage and guide teachers and other staff, and have the ability to form collaboration between fellow teaching staff and with related agencies. (2) educational management innovation process at MAN Kandangan Kab. Kediri includes innovations in the field of curriculum, namely changes to the 1994 curriculum to a competency-based curriculum and a full day entry system from 06.45-15.05, facilities and infrastructure, namely the addition of school buildings and the addition of 5 computer units, library books, financial management, teaching and learning strategies, student management, and management of teaching staff. (3) About the factors that support and inhibit the leadership of school principals in carrying out educational management innovations at MAN Kandangan District. Kediri is: supporting factors: the persistence of the efforts of the teaching staff at MAN Kandangan Kab. Kediri in creating quality madrasas that are able to answer future challenges, internal and external factors where internal factors include school principals, teachers, students, while external factors include parents and a conducive environment, education system factors, the existence of short-term and long-term planning . Short-term planning, for example: improving the curriculum, while long-term planning, for example: building and adding school buildings, and so on. Meanwhile, the inhibiting factors are the lack of available funds and limited facilities and infrastructure. However, this can be covered by providing funds through mandatory donations from student parents, as well as requests for subsidies from the government.